2015
DOI: 10.1016/j.jval.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

What Guidance are Economists Given on How to Present Economic Evaluations for Policymakers? A Systematic Review

Abstract: Health economists have consistent presentation formats and common reporting elements that should be considered when developing user-friendly explanations for general audiences. These overlap with policymakers' informational needs but may not be sufficient for understanding by nontechnical audiences. Developing presentation formats and tools that incorporate viewpoints of both economists and noneconomists will allow for better application of the results of economic evaluations and enhance the transparency and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In combination with traditional health indicators such as mortality and morbidity, a comprehensive indicator (e.g. quality-adjusted life years or QALYs) can be calculated to inform clinical, funding, public policy and management decisions on health products and technologies [913].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with traditional health indicators such as mortality and morbidity, a comprehensive indicator (e.g. quality-adjusted life years or QALYs) can be calculated to inform clinical, funding, public policy and management decisions on health products and technologies [913].…”
Section: Introductionmentioning
confidence: 99%
“…This was done to ensure that we present information that is useful to decision-makers and has been a driver in our decision to report the results as a PBMA. Reporting results over different time horizons and for a range of outcomes, not just QALYs, has also been recommended when reporting results for decision-makers [ 7 , 28 ]. Previous research has suggested that decision-makers rarely use QALYs, preferring hard clinical outcomes instead as they find them easier to understand [ 23 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reporting results over different time horizons and for a range of outcomes, not just QALYs, has also been recommended when reporting results for decision-makers [ 7 , 28 ]. Previous research has suggested that decision-makers rarely use QALYs, preferring hard clinical outcomes instead as they find them easier to understand [ 23 , 28 ]. However, we have chosen to keep with QALYs given these can capture both mortality and morbidity – an important consideration in stroke care, which aims to improve functioning in addition to extending life.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting guidance focuses on providing transparent costeffectiveness information. This includes reporting study methods such as perspective, population, time horizon, effectiveness source, benefit measurement, study type, model type, SAs (both a list of parameters and range of ICERs), and base-case deterministic and probabilistic results [18]. Table 3 describes the methods used for reporting study results in the rapid review.…”
Section: Current Guidelinesmentioning
confidence: 99%